On Supplement -Small Submodules - Sagban, Manal A.; Yassen, Sahira M. (Iraqi Journal of Science, 2026)
This paper studied a supplement-small submodule, which is generalization of the small submodule. We present a characterization for the supplement-small submodule. We give an important property of this kind of sub module, also the concept of supplement-small radical of  R module is investigated.